Clinical Characteristics and Potential Mechanisms in Patients with Abnormal Liver Function Indices and Elevated Serum IgG4 - Jing Wang; Yue Zhang; Dandan Jiang; Lu Zhou; Bangmao Wang (Canadian Journal of Gastroenterology and Hepatology)
Objective. We analyzed the etiological classification and clinical characteristics of patients with abnormal liver function indices and elevated serum IgG4 levels and investigated the effects of intrahepatic follicular helper T cell (Tfh) infiltration and serum IL-21. Methods. Clinical data (age, sex, past history, clinical manifestations, laboratory tests, imaging, diagnosis, and treatment) and etiology of liver injury from 136 patients were analyzed. We compared the general condition, clinical characteristics, and laboratory tests of 19 AIH (autoimmune hepatitis) patients with elevated serum IgG4 levels with those of 20 AIH patients with normal serum IgG4 levels admitted at the same time. Five patients with AIH and elevated serum IgG4 levels and five AIH patients with normal IgG4 levels were matched by sex, age, and liver function, and Tfh infiltration in liver biopsy tissues of patients in both groups was determined by immunofluorescence staining. Five AIH patients with elevated serum IgG4 levels were selected for measurement of serum interleukin-21 (IL-21) levels by enzyme-linked immunosorbent assay (ELISA), seventeen AIH patients with normal serum IgG4 were matched by sex, age, and liver function indices, and 29 physically healthy individuals matched by sex and age were selected as the control group. The changes in patients with IgG4-RD and abnormal liver function before and after glucocorticoid treatment were measured. Results. Patients (136) with abnormal liver function indices and elevated serum IgG4 levels were diagnosed with liver disease of different etiologies. IgG4-related disease was the most frequent, followed by AIH and malignancy. Abnormal liver function indices with high serum IgG4 were most commonly seen as elevated gamma glutamyl transferase (GGT). The AIH group with elevated serum IgG4 had increased intrahepatic levels of Tfh. IL-21 in AIH patients with elevated IgG4 was higher than in patients with normal IgG4 and healthy controls. Patients (n = 28) with abnormal liver function indices and IgG4-related disease received glucocorticoid therapy for six months, and ALT, AST, ALKP, GGT, TBil, DBil, IgG, IgG4, and IgE were significantly lower after treatment. Conclusions. Elevated serum IgG4 was seen in patients with abnormal liver function indices with diverse causes. Tfh infiltration and increased IL-21 production may be related to the pathogenesis of AIH with elevated serum IgG4. Glucocorticoid therapy is effective in patients with abnormal liver function indices and IgG4-related disease. Assessing immune function in patients with abnormal liver function indices and elevated serum IgG4 levels should facilitate diagnosis and treatment of the disease.